2020
DOI: 10.1177/1178622120969658
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Removal of Phosphate From Wastewater Using Ethiopian Rift Pumice: Batch Experiment

Abstract: Phosphorous from municipal and industrial wastewater is the main cause of eutrophication of rivers and lakes, because effluent quality from conventional secondary wastewater treatment plants does not meet the discharge standard that demands further treatment. Therefore, we investigated pumice as a potential low-cost adsorbent for the tertiary treatment of phosphate from municipal wastewater. The phosphate adsorption process reached equilibrium after 60 minutes contact time and achieved a removal efficiency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…These two reports were focused on stormwater. In addition, batch experiment conducted by Fetene and Addis (2020) reported that pumice removed 95% phosphate from secondary treatment of municipal wastewater. Çifçi and Meriç (2016) evaluated the application of pumice for treated wastewater and concluded that adsorption mechanisms play an important role for pollutant removal.…”
Section: Introductionmentioning
confidence: 99%
“…These two reports were focused on stormwater. In addition, batch experiment conducted by Fetene and Addis (2020) reported that pumice removed 95% phosphate from secondary treatment of municipal wastewater. Çifçi and Meriç (2016) evaluated the application of pumice for treated wastewater and concluded that adsorption mechanisms play an important role for pollutant removal.…”
Section: Introductionmentioning
confidence: 99%
“…(BK2). Fetene and Addis [16] have demonstrated the removal of phosphate from wastewater using Ethiopian rift pumice. A comprehensive study on phosphate removal from water using phragmites australis biochar loaded with aluminum, calcium, iron, lanthanum, and magnesium oxides was studied by Wang et al [17].…”
Section: Introductionmentioning
confidence: 99%